Sustainability and innovation in an educational context - Szilágyi, Tamás; Dudok, Fanni (Acta Cultura et Paedagogicae, 2023)
Innovation and sustainability will be of utmost importance in the educational workshops of the next decades and will necessitate distinct techniques and specialised skills. Regarding education, sustainability, and environmental awareness, the European Union has issued a number of suggestions to its Member States. These proposals include objectives such as incorporating sustainability into teaching and learning, integrating environmental consciousness into the education system as a whole, and supporting the acquisition of awareness, comprehension, and action-based competencies. Innovation in education is essential to modernising the nation's educational system and preparing pupils for the future. Developing an inventive mentality is a crucial objective of education, as it stimulates creativity, the development of problem-solving abilities, and the capacity to adapt to rapid change. Sustainability and innovation are essential components of contemporary education because they help students prepare for the future, provide chances for practical learning, improve career preparation, and increase environmental consciousness. Students that incorporate these ideas into their schooling will be better equipped to face future obstacles and capture opportunities.